The Difficulty of Students in Utilizing Online Learning Resources to Apply Creative Thinking - Puji Luritawaty, Irena; Prabawanto, Sufyani; Herman, Tatang (KnE Social Sciences, 2024)
Creative thinking skills can create creative ways and harmonize knowledge with time. However, the analysis of the difficulties of mathematics education students has not been widely discussed, especially in the use of online learning resources. This study analyzes 15 fourth-semester mathematics education students’ difficulties in using online learning resources to apply creative thinking in solving math problems. Instruments consist of creative thinking skills test and a scale of online learning difficulties. The study results found that all subjects were familiar with online learning resources. However, its utilization was still minimal due to various difficulties, such as unstable signals, high quota costs, confusion about choosing an abundance of information, and uncertainty about the correctness of the information. These difficulties have an impact on the limited knowledge of the subject and the ability to generate ideas. Fluency in creative thinking was low. Subject ideas tend to be limited and routine. Subjects prefer to present an idea and immediately apply it to problem-solving. Flexibility is not visible, and errors in responding to ideas still occur. As a result, when the idea is executed incorrectly, the problem-solving is also wrong. Keywords: difficulty of student, online learning resource, creative thinking